Development of Leseübungen Materials and Text Comprehension Strategies Based on Student Feedback at the B1 Level - Surya Masniari Hutagalung; Herman Syahputra (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2026)
This study aimed to develop Leseübungen materials and text comprehension strategies based on student feedback for B1-level German language learning in the German Language Education Study Program at Universitas Negeri Medan. The study was motivated by the low student pass rate in the Lesen module, which was caused by limited vocabulary mastery, difficulties in understanding sentence structures, ineffective reading strategies, and low comprehension of textual contexts. The research employed the Design-Based Research method using Reeves’ model, which consists of four stages: collaboration with practitioners, identification of solutions, evaluation, and revision. Based on the results of the analysis, Leseübungen materials grounded in Student-Centered Learning (SCL) were developed by integrating collaborative strategies. The developed materials were validated by three experts and achieved an average Aiken’s V score of 0.93, categorized as highly valid. The implementation phase involved 20 students from the B1 Vorbereitung class. The findings revealed a significant improvement in students’ Lesen abilities. The mean pre-test score increased from 46.25 to 63.90 in the post-test, with the paired sample t-test showing t = 9.44 and a significance value of p < 0.05. The findings indicate that the development of Leseübungen materials based on student feedback was effective in improving B1-level German text comprehension skills. The development of learning materials tailored to students’ needs, combined with collaborative strategies and the integration of learning technologies, contributed to improved global and detailed text comprehension and supported the enhancement of German language learning quality in higher education.